Reflection Phase Characterization of Metasurfaces Enabling Reflection and Transmission in Wireless Systems - Rajkumar Maniam; Thennarasan Sabapathy; Mohamed Nasrun Osman; Muzammil Jusoh; SIDDARTH PICHANDI (Geviva Publisher, 2025)
This paper presents the design and analysis of metasurfaces for surface-based wireless communication systems. Metasurfaces are widely used as reflecting or transmitting surfaces in wireless communications. The reflection phase characteristic of a metasurface plays an important role in determining its operating behavior, namely whether it functions as a reflector or a transmitter. In this work, a comprehensive analysis is conducted to obtain two distinct reflection phase characteristics of metasurface unit cells. The unit cells are analyzed at an operating frequency of 3.5 GHz. It is observed that the unit cell exhibits a reflection phase close to 0° when designed using two rectangular rings, while a reflection phase close to 180° is achieved when the unit cell is modeled as a square ring. In both designs, the unit-cell substrate size is fixed at 16.25 × 16.25 mm². The presented reflection phase characterization provides a clear design guideline for selecting metasurface unit-cell geometries to support reflection and transmission functionalities in future surface-based wireless communication systems.